PELATIHAN PEMASANGAN PHOTO SEL UNTUK INSTALASI PENERANGAN DAN SOSIALISASI PENGHEMATAN ENERGI - Damis Hardiantono; Paulus Mangera (Musamus Devotion Journal, 2020)
Sermayam Indah Village located on Districk of Tanah Miring – Merauke is one area where the development of electricity needs continues to grow, especially in the household sector and so far the main supply has been supplied by PT. PLN (Persero) UP3 Merauke but it was not followed by improvements of lighting installations that installed in the houses of the village. Outcomes in this activity is carried out in 2 (two) activity schemes in accordance with the situation analysis that has been carried out, namely: the training scheme and the socialization scheme. The training begins with a theoretical introduction followed by direct experiment. The socialization about saving of electrical energy, especially in the lighting installation of village houses and carried out attractively invited the public to be invited to raise issues related to the use of electricity. The impact of the activities, are: 1) Sermayam Indah Village community has been able to independently install a photo sell as an automatic device, especially for lighting the porch lights of the house or building; 2) The community has understood the technical installation of the correct installation both in terms of material and technical connection with proven from the beginning of the lightning installation which carelessly became an installation in accordance with safety standards